THE EFFECT SELF EFFICACY AND COMPETENCE ON ENTREPRENEURIAL INTENTIONS WITH COPING AS MEDIATION - Zulhawati; Pujiastuti; Rofiqoh, Ifah; Diana Sari, Septi (Universitas Teknologi Yogyakarta, 2019)
Abstract— The purpose of this study was to examine the effect of self-efficacy and competence on the intention toentrepreneurship by coping as a mediating variable. Self-efficacy is the level of confidence in doing the task well,competence is the ability, knowledge / understanding, and attitude needed in carrying out job responsibilities. Copingas a behavioral and cognitive effort in managing internal and external demands is expected to overload and exceedindividual abilities. The sample in this study were Yogyakarta Technological University (UTY) students who weredivided into three groups, namely students who had never received entrepreneurship courses, had already receivedcourses, entrepreneurship, and students who had obtained courses, entrepreneurship who had just joined theEntrepreneurship Development Program. The results of the study showed that self-efficacy, competence and copinginfluenced the desire for entrepreneurship. Self-efficacy and competence have an indirect positive effect onentrepreneurial intentions through coping.